Poor rates of linkage to HIV care and uptake of treatment after home-based HIV testing among newly diagnosed 15-to-49 year-old men and women in a high HIV prevalence setting in South Africa. Issue 1 (2nd January 2021) - Maughan-Brown, Brendan; Beckett, Sean; Kharsany, Ayesha B. M.; Cawood, Cherie; Khanyile, David; Lewis, Lara; Venkataramani, Atheendar; George, Gavin
ABSTRACT: Early antiretroviral therapy (ART) initiation is essential, but linkage to care following community-based services is often poor, and inadequately understood. This study examined factors influencing linkage to care following home-based HIV-testing services (HBHTS) in a hyper-endemic setting in South Africa. HBHTS was offered to participants ( N  = 10, 236) enrolled in the second HIV Incidence Provincial Surveillance System survey (2015–2016), KwaZulu-Natal. Follow-up telephone surveys with 196 of the 313 individuals diagnosed HIV-positive through HBHTS were used to measure linkage to care (i.e., a clinic visit within 12 weeks) and ART-initiation. Among newly diagnosed individuals ( N  = 183), 55% linked to care, and 21% of those who were ART-eligible started treatment within 12 weeks. Linkage to care was less likely among participants who had doubted their HIV-diagnosis (aOR:0.46, 95%CI: 0.23–0.93) and more likely among participants who had disclosed their HIV-status (aOR:2.31, 95%CI: 1.07–4.97). Reasons for not linking to care included no time (61%), only wanting to start treatment when sick (48%), fear of side-effects (33%), and not believing the HIV-diagnosis (16%). Results indicate that HBHTS needs to be paired with targeted interventions to facilitate early linkage to care. Interventions are required to counter denial of HIV status and facilitate early linkage to care among healthier individuals.